INTEGRASI KONSEP MODERASI BERAGAMA DALAM PENGEMBANGAN MATERI PENDIDIKAN AGAMA ISLAM - Nur Fazillah Nur Fazillah (lembaga Sepercenter, 2024)
Religious moderation is an important approach in facing the challenges of Indonesia's multicultural society. Islamic Religious Education (PAI) as a core subject in schools has a strategic role in instilling moderate attitudes from an early age. This study aims to analyse how the concept of religious moderation can be integrated into the development of PAI materials so that learning is more contextual, inclusive, and relevant to students' lives. The research method used is library research by reviewing relevant literature, regulations, and curricula. The results of the study show that the integration of religious moderation in PAI can be done through three main aspects: (1) selection of materials that promote the values of tolerance, justice, and balance; (2) application of dialogical and participatory learning methods; and (3) strengthening of character-based evaluation. Thus, the development of PAI materials based on religious moderation is expected to shape a generation of Muslims who are broad-minded, respect differences, and contribute to the creation of social harmony.